Analysis of Business Feasibility Study on Florist and Gift Liia Store Reviewed from Technical or Operational Aspects: Analisis Studi Kelayakan Bisnis pada Florist and Gift Liia Store Ditinjau dari Aspek Teknis atau Operasional - Husnul khotimah; Abdur Rohman (PT Syamilah Literasi Islami, 2024)
Before deciding to start a project or business, it is necessary to have a feasibility study analysis on the business. A feasibility study is needed to determine if the idea or ideas are feasible. So that the business or business can later run well according to plan and not deviate too much and obtain sufficient profits to achieve business goals and also minimize errors and obstacles in the business or business, especially in technical or operational aspects. This study aims to analyze the business feasibility study on the florist and gift Liia store business from the technical or operational aspect. The research method used is a qualitative descriptive method, research In this case, the data used are secondary and primary data. The primary data source of this research is the results of interviews while the secondary data sources are journals and books. The results of this study show that the Florist and Gift Store business is feasible to run from a technical or operational aspect.